Assessment of Anesthetic and Resuscitative Care in Patients with Acute Coronary Syndrome at Aortocoronary Bypass Surgery - V. V. Moroz; D. Yu. Spirochkin (Общая реаниматология, 2007)
Objective: on the basis of the data available in the literature to develop a system of criteria for assessing the quality of anesthetic and resuscitative care at aortocoronary bypass surgery (ACBS) in patients with acute coronary syndrome (ACS).Materials and methods: the medical records of patients with different forms of ACS, undergone surgical myocardial revascularization, were analyzed. The current references on the intensive care and surgical treatment of ACS were studied and analyzed.Results: a score system of criteria for assessing the quality of anesthesiological and reanimatological care is presented and warranted for ACS patients. The system characterizes the quality of preoperative preparation, anesthesia, intensive care, postoperative surgical unit stay, and treatment outcome. Possible areas of application of this system are indicated.Conclusion: The elaborated criterion system may be used in evaluating the efficiency of new procedures, surgical techniques and interventions, medical equipment and in comparing the groups of patients selected by a definite sign.